Exploring the critical success factors for the implementation of the vehicle useful life (scrappage) component of the DOTr's PUV modernization program - Pontawe, Joemier D. (School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
This study focused on exploring the critical success factors for the implementation of the Vehicle Useful Life (Scrappage) component of the DOTr's PUV Modernization Program. The study was divided into two parts. The first sub-study analyzed the relationship between the effectivity of vehicle modernization programs and factors such as government allocated budget, incentives (minimum and maximum), minimum vehicle age requirement, and program duration. The researcher gathered secondary data on 84 past vehicle modernization programs across 30 countries implemented from 1990 to 2017. Pearson correlation and linear regression analyses were then used to determine the relationship between the effectivity of the modernization program (measured by the number of vehicles scrapped) as dependent variable and the aforementioned factors as independent variables. The results of the analyses revealed that the government allocated budget has a strong positive linear relationship with the effectivity of modernization programs while the minimum vehicle age requirement has a moderate negative linear relationship with the latter. Then, the second sub-study applied the five best practices of the International Council on Clean Transportation (ICCT) in reducing emissions through vehicle replacement programs in assessing the responsive vehicle modernization and scrappage programs of Egypt, France, japan India the US, and the Philippines' PUV Modernization Program. Results of this sub-study suggested that out of the six programs assessed, the Heavy-Duty fleet modernization program of India is the most compliant program to the 5 best practices. Meanwhile, the US's CARS program was the least compliant, which partially complied to only two of the best practices. The Philippines' PUV Modernization Program on the other hand was compliant to two best practices, partially compliant to the other two, and was tagged as non-compliant to one best practice. Lastly, a case study of 1 TEAM, a transport group which was able to modernize several PUJ units ahead of the implementation of the modernization program, was conducted in order to supplement the results of the two sub-studies. Surveys and key informant interviews were conducted for the said case study. All 20 operators who own the 30 brand new Euro 2 jeepneys operated by the transport group participated in the survey. Meanwhile, Mr. Yuri Sarmiento, President of 1TEAM, was also interviewed to validate and supplement the output of the survey. Results of the case study revealed that the PUJ operators received higher income after they modernized their jeepneys. The results also suggest that it is financially viable to modernize the jeepneys and at the same time provide fixed salaries to drivers and other personnel such as conductors, mechanics, safety officers, dispatchers, etc., provided that an efficient fleet management is observed and that routes are rationalized. based on these findings, the author recommends that the DOTr revisit the budget allocation for the implementation of the PUV Modernization program and the amount of financial incentive/ subsidy which the Department currently offers. Further, additional non-fiscal incentives must also be provided, alongside the provision of intensive training on fleet management and financial literacy for existing transport groups and individual jeepney operators.